Teaching effective use of words for vigor in style - Remolona, Paciencia Mendiola 1923- (1968)
This study presents the following: the relation between style and the mastery of words, the five requirements for effective use of words, and the teaching tools and samplings of instructional materials. It also suggests four teaching techniques - the slang approach, the emotional precision, the dicto-comp springboard, and the advertising touchstones. Each technique is accompanied by graded exercises to show the composition teacher how systematic guidance in conscious choice and use of words can lead to improved student compositions.